Early Spontaneous Abdominal Bleeding is associated with Poor Outcome in Moderate to Severe Acute Pancreatitis Patients: A Propensity Matched Study - Chen, Yizhe (Sci Rep, 2017)
Abdominal bleeding is a lethal complication in acute pancreatitis (AP) and it is commonly described as a late event. However, spontaneous intra-abdominal bleeding could occur very early but no study focusing on this phenomenon was published yet. In this study, 1137 AP patients were retrospectively screened and 24 subjects suffering early spontaneous bleeding (ESB) were selected. Meanwhile, a 1:1 well-balanced cohort of non-bleeding patients was generated by propensity score match. The clinical characteristics of these patients were compared and a multiple regression analysis was performed to assess the risk factors for ESB. Besides, patients with massive post-intervention bleeding (PIB) were collected for additional comparison. ESB patients suffered significantly worse outcome than the matched cohort evidenced by dramatically higher mortality than the non-bleeding patients and even the PIB group (54.2% versus 20.8%, P = 0.017; 54.2% versus 31.0%, P = 0.049). The regression analysis demonstrated computer tomography severity index (CTSI; OR, 3.34; 95% CI, 1.995–5.59, P < 0.001) and creatinine (OR, 1.008; 95% CI, 1.004–1.012, P < 0.001) were associated with the occurrence of ESB. In conclusion, ESB is a rare but dangerous complication of moderate-to-severe AP and may result in high mortality. CTSI and creatinine are independent risk factors for the development of ESB.